The Relationship Between Platelet Count and Albumin Levels with the Severity of DHF Patients - Angki Purwanti; Tri Presetyorini; Dhony Wiedyanto Kasongko (CV. CENDIKIA JENIUS INDONESIA, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia and is characterized by bleeding manifestations, thrombocytopenia, and decreased serum albumin levels. This study aimed to analyze the relationship between platelet count, albumin level, gender, and age category with the severity of DHF. An observational analytic study with a cross-sectional design was conducted using secondary data from 64 DHF patients at Anugerah Sehat Afiat Regional Hospital. Data were analyzed using Pearson correlation, Fisher’s Exact test, and Monte Carlo test with a 95% confidence level. The results showed significant associations between platelet count (p<0.001; r=-0.427) and serum albumin level (p<0.001; r=-0.625) with DHF severity. However, no significant association was found between platelet count and albumin level (p=0.101), nor between gender (p=0.788) and age category (p=0.768) with DHF severity. In conclusion, platelet count and serum albumin level were associated with DHF severity, whereas gender, age category, and the relationship between platelet count and albumin level were not. Future studies are recommended to include additional clinical and laboratory parameters to improve the accuracy of DHF severity prediction.